2018
DOI: 10.1177/1055665618754947
|View full text |Cite
|
Sign up to set email alerts
|

An Intercenter Comparison of Nasolabial Appearance Including a Center Using Nasoalveolar Molding

Abstract: The protocol followed by center G, the only center that performed NAM and primary nasal reconstruction, produced better results in all categories when compared to center C, the only center that did not perform presurgical orthopedics or lip/nose revisions. When compared to centers that performed traditional presurgical orthopedics and surgical revisions (B and D), center G was not consistently better in all categories. As with other uncontrolled, retrospective intercenter studies, it is not possible to attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
2
22
2
Order By: Relevance
“…A total of 439 publications were identified, and 13 publications met criteria for inclusion in this review (Figure 1) (Barillas, 2009; Chang et al, 2010; Clark, 2011; Shetty, 2017; Akarsu-Guven, 2018; AlHayyan et al, 2018; Kornbluth, 2018; Massie, 2018; Peanchitlertkajorn, 2018a; Peanchitlertkajorn, 2018b; Singer, 2018; Funayama et al, 2019). The fully reproducible search strategy is included in the Online Appendix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 439 publications were identified, and 13 publications met criteria for inclusion in this review (Figure 1) (Barillas, 2009; Chang et al, 2010; Clark, 2011; Shetty, 2017; Akarsu-Guven, 2018; AlHayyan et al, 2018; Kornbluth, 2018; Massie, 2018; Peanchitlertkajorn, 2018a; Peanchitlertkajorn, 2018b; Singer, 2018; Funayama et al, 2019). The fully reproducible search strategy is included in the Online Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…The fully reproducible search strategy is included in the Online Appendix. The 2 publications by Peanchitlertkajorn et al (Peanchitlertkajorn, 2018a; Peanchitlertkajorn, 2018b) were retrospective analyses that included the same 4 centers: Centers B, C, and D of the original Americleft study (Long et al, 2011) and one additional center that offered NAM (center G). Although these publications assessed different outcomes, they were considered to represent a single patient sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the alveolar gap width and transverse dental arch relationships have been described by different groups following primary cheiloplasty. 24 , 31 , 32 These authors reported that presurgical orthopedics had no lasting effect on arch form.…”
Section: Discussionmentioning
confidence: 98%
“…The Americleft study found no significant differences in nasolabial outcomes across four centres for both total and individual subscale component of the AM . However, a further study, which included three of the original centres plus an additional new centre, suggested that there may be an association with various treatment protocols …”
Section: Introductionmentioning
confidence: 89%